2021
DOI: 10.1186/s13071-021-04632-6
|View full text |Cite
|
Sign up to set email alerts
|

Probable contribution of Culex quinquefasciatus mosquitoes to the circulation of chikungunya virus during an outbreak in Mombasa County, Kenya, 2017–2018

Abstract: Background Chikungunya virus is an alphavirus, primarily transmitted by Aedes aegypti and Ae. albopictus. In late 2017–2018, an outbreak of chikungunya occurred in Mombasa county, Kenya, and investigations were conducted to establish associated entomological risk factors. Methods Homes were stratified and water-filled containers inspected for immature Ae. aegypti, and larval indices were calculated. Adult mosquitoes were collected in the same homes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Since evidence shows that this species is not able to transmit CHIKV [20], this result can only highlight the hyperendemicity found in that area. Similar findings were reported by Cruz et al (2020) [6] in Brazil and Lutomiah et al (2021) [34] in Kenya, who reported CHIKV-positive when analyzing whole-body C. quinquefasciatus derived from field collections.…”
Section: Discussionsupporting
confidence: 88%
“…Since evidence shows that this species is not able to transmit CHIKV [20], this result can only highlight the hyperendemicity found in that area. Similar findings were reported by Cruz et al (2020) [6] in Brazil and Lutomiah et al (2021) [34] in Kenya, who reported CHIKV-positive when analyzing whole-body C. quinquefasciatus derived from field collections.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, in the large-scale outbreak of IOL sub-lineage E1-K211E/E2-V264A carrying E1-I317V in Thailand during 2018-2020, Aedes aegypti was identified as the primary vector, and viral RNA was also found in another mosquito species, Culex quinquefasciatus [50,51]. In Mombasa, Kenya, these two mosquito species might have played a role in the outbreak of IOL sub-lineage E1-K211E/E2-V264A/E1-I317V [41,52]. Whether this mutation has a functional role in viral adaptation to Aedes aegypti or other mosquito species needs to be clarified by further studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus pool positive for CHIKV RNA suggests the potential for transovarian or sexual transmission, as previously suggested [13,14]. In Kenya, Lutomiah et al [15] proposed the involvement of Cx. quinquefasciatus in CHIKV transmission based on the discovery of naturally infected mosquitoes and evidence of high vector competency in laboratory assays.…”
Section: Discussionmentioning
confidence: 56%
“…albopictus are highly competent for transmitting CHIKV [8,9] and have spread widely since their introduction in 1986 [10][11][12]. Additionally, urban areas in Brazil are infested with Culex quinquefasciatus, which has been found naturally infected by CHIKV [6,13,14], although its vector competence is controversial [15,16].…”
Section: Introductionmentioning
confidence: 99%